CSR Web Communication by Controversial Enterprises in the Context of Stakeholder and Legitimacy Theories - Kopřiva, Jan; Tetřevová, Liběna; Záhorská, Alexandra (Univerzita Hradec Králové, 2022)
The study of CSR communication and CSR web communication is based on many theories. The most frequently mentioned of these is stakeholder theory and, in the context of controversial enterprises, legitimacy theory. This article aims to assess whether controversial enterprises, such as chemical enterprises, operating in selected countries communicate their socially-responsible behavior in line with stakeholder and/or legitimacy theories. The subject of this study was the TOP chemical enterprises located in Czechia, Norway, Slovakia, and Ukraine. Descriptive and inferential statistical tools were used to process the data obtained from content analysis. From a methodological point of view, “The Method of Communication of Economic, Environmental, Ethical, Social and Philanthropic Activities” was used. The study which was performed shows that the TOP chemical enterprises in Czechia, Norway, Slovakia, and Ukraine communicate environmentally-responsible and economically-responsible measures to the greatest extent on their web pages. This confirmed the hypothesis that environmentally sensitive enterprises communicate their CSR measures in line with legitimacy and stakeholder theories.
CSR web komunikování kontraverzních firem v kontextu stakeholder a legitimity teorií
Keywords: stakeholder theory; legitimacy theory; corporate social responsibility; web communication; stakeholder teorie; teorie legitimity; společenská odpovědnost firem; web komunikování